Enhanced image contrast with delocalized near‐field excitation. Issue 9 (6th January 2014) - Sánchez, E.; Dunham, A.; Nowak, D.; Straton, J.; Doughty, J.
<x xml:space="preserve">Abstract</x> Making highly resonant tip geometries via nanofabrication can be a difficult process, while the aperture/detector method is a much easier to implement. With this technique, even tips with undesirably low resonance can be utilized for imaging. We demonstrate the concept through the use of a low field enhancement probe by showing the spatial separation of the excitation and field enhancement locations and the associated numerical modeling. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>